Availability of Power Flow Doppler Imaging for Visualization of Intracranial Vascular Structures and the Brain Circulation in Neonates - ICHIYAMA, Takashi; HAYASHI, Takashi; NISHIKAWA, Miki; NAKASHIMA, Kanae; KANEKO, Junko; FURUKAWA, Susumu (Neurosonology, 1998)
We attempted to evaluate intracranial cerebral vessels in neonates using a newly developed power flow Doppler imaging method. Four normal- term neonates were examined through the anterior fontanel. The artery system, including the anterior cerebral, middle cerebral, posterior cerebral, basilar and lenticulostriate arteries, was well visualized in all subjects. The venous system, including the internal cerebral vein, Galen vein, and straight and transverse sinuses, was also clearly demonstrated in all cases. Power flow methods clearly revealed slow- flow vessels and small vessels, which could not be demonstrated by conventional color Doppler methods. The middle cerebral artery, which crossed the ultrasound beam vertically, was visualized by the power flow method. We also examined the blood flow velocities at three points of the lenticulostriate artery (LSA) by pulsed Doppler under guiding power flow imaging. The maximum and minimum flow velocities decreased gradually from the central to the peripheral portion. The resistance indices and pulsatility indices at each position were not significantly different. These findings suggest that measurement of the LSA can be used to evaluate the peripheral circulation in a focal region of the brain.